Electrophysiological abnormalities in induced pluripotent stem cell‐derived cardiomyocytes generated from Duchenne muscular dystrophy patients. Issue 3 (8th January 2019) - Eisen, Binyamin; Ben Jehuda, Ronen; Cuttitta, Ashley J.; Mekies, Lucy N.; Shemer, Yuval; Baskin, Polina; Reiter, Irina; Willi, Lubna; Freimark, Dov; Gherghiceanu, Mihaela; Monserrat, Lorenzo; Scherr, Michaela; et al.
Abstract: Duchenne muscular dystrophy (DMD) is an X‐linked progressive muscle degenerative disease, caused by mutations in the dystrophin gene and resulting in death because of respiratory or cardiac failure. To investigate the cardiac cellular manifestation of DMD, we generated induced pluripotent stem cells (iPSCs) and iPSC‐derived cardiomyocytes (iPSC‐CMs) from two DMD patients: a male and female manifesting heterozygous carrier. Dystrophin mRNA and protein expression were analysed by qRT‐PCR, RNAseq, Western blot and immunofluorescence staining. For comprehensive electrophysiological analysis, current and voltage clamp were used to record transmembrane action potentials and ion currents, respectively. Microelectrode array was used to record extracellular electrograms. X‐inactive specific transcript (XIST) and dystrophin expression analyses revealed that female iPSCs underwent X chromosome reactivation (XCR) or erosion of X chromosome inactivation, which was maintained in female iPSC‐CMs displaying mixed X chromosome expression of wild type (WT) and mutated alleles. Both DMD female and male iPSC‐CMs presented low spontaneous firing rate, arrhythmias and prolonged action potential duration. DMD female iPSC‐CMs displayed increased beat rate variability (BRV). DMD male iPSC‐CMs manifested decreased I f density, and DMD female and male iPSC‐CMs showed increased I Ca, L density. Our findings demonstrate cellular mechanisms underlying electrophysiological abnormalities and cardiac arrhythmias in DMD.